Handbook of nanophase materials - Goldstein, Avery N. (Marcel Dekker, 1997)
"Integrates current research on submicron-sized domain materials. Provides fundamental insight into particle size control and nanophase methodologies and materials--addressing specific problems in a host of research fields, including chemistry, physics, materials science, and engineering."